Kajian Macam Pupuk Kandang Terhadap Intensitas Penyakit Bercak Daun (Bipolaris Maydis Syn.) Pada 3 Jenis Jagung (Zea Mays L.) - Asgoro, Bayu; Santoso, Sartono Joko; Hardiatmi, Sri (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
The research about study Kinds of Manure on the intensity of Leaf Spots (Bipolaris Maydis Syn.) On 3 Types of Corn (Zea Mays L). with the aim to1study1the type of manure on the intensity of Bipolaris Maydis Syn leaf spot on three maize varieties (Zea Mays L) which was carried out from 4 November 2019 to 17 January 2020, in Siderejo Hamlet, Sajen Village, Trucuk District, Klaten Regency, with altitude of 130m above sea level. This research uses factorial completely randomized complete block design (RCBD) which is arranged in a Split plot consisting of 2 treatment factors with 12 treatment combinations.The parameters observed are (1) Disease, namely symptoms of attack and intensity of attack. (2) The yield includes the weight of the cob per plant, the number of cob, the length of the cob and the diameter of the cob. Data from this study were analyzed with the LSD test (the Smallest Significant Difference) at a level of 5%. The results of the research : (1) Symptoms of leaf spot disease appear evenly on yellow and black corn varieties, symptoms of disease attack appear at 6 weeks after planting in all varieties. (2) The treatment of manure on black corn (V3P3) affected the intensity of leaf spot disease by 27.70. (3) The treatment of chicken manure on black corn (V3P3) with the highest leaf spot intensity gave a low yield but had no effect compared to goat manure and control. (4) The treatment of manure on yellow corn (V1) significantly affects the weight of fresh cobs. Treatment of kinds of manure with the type of white corn (V2) significantly affected the weight of fresh cobs per crop, length of cobs and number of cobs. Treatment of kinds of manure with the type of black corn (V3) significantly affects the diameter of the cobs